Preparation method and application of III-type eutectic solvent modified peanut shell-based hydrothermal carbon heavy metal ion adsorbent

A one-step hydrothermal method using a low eutectic solvent modifies peanut shells to produce a carbon material with high Cr(VI) adsorption capacity and fast kinetics, addressing the limitations of existing methods by simplifying the process and enhancing performance.

CN119215851APending Publication Date: 2024-12-31GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411075940.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing methods for preparing peanut shell-based carbon materials for Cr(VI) adsorption are costly, complex, and have limited adsorption capacity and kinetics, while using toxic gemini surfactants complicate the process.

Method used

A one-step hydrothermal method using a low eutectic solvent composed of choline chloride and urea modifies peanut shell powder to produce a hydrothermal carbon material with enhanced Cr(VI) adsorption capacity and kinetics, utilizing a simple and environmentally friendly process.

Benefits of technology

The method results in a hydrothermal carbon material with large adsorption capacity and fast adsorption kinetics for Cr(VI), achieving high equilibrium adsorption amounts and rapid equilibrium times, while using inexpensive and abundant raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215851A_ABST
    Figure CN119215851A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation and application of carbon-based composite functional materials, and particularly relates to a preparation method and application of a class III eutectic solvent modified peanut shell-based hydrothermal carbon heavy metal ion adsorbent. The method comprises the following steps: adding peanut shell powder into a deep-eutectic solvent, uniformly mixing to form a turbid liquid, then adding a certain amount of deionized water into the turbid liquid at room temperature, and stirring for a period of time; carrying out hydrothermal carbonization reaction on the mixture after stirring, and cooling the product to room temperature after the reaction is finished; and separating, washing and drying the product to obtain the hydrothermal carbon material. The peanut shell-based hydrothermal carbon material is prepared by modifying the deep-eutectic solvent, and has the remarkable advantages of fast adsorption kinetics, high equilibrium adsorption capacity and the like on Cr (VI) pollutants in wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation and application of carbon-based composite adsorption materials, and specifically relates to a preparation method and application of a type III low eutectic solvent modified peanut shell-based hydrothermal carbon heavy metal ion adsorbent. Background Art

[0002] Water pollution caused by chromium and its compounds mainly comes from inferior cosmetic raw materials, leather preparations, chrome-plated parts of metal parts, industrial pigments, and tanning, rubber and ceramic raw materials. Chromium in water mainly exists in the form of Cr(VI). If it is accidentally ingested or drunk, it can cause poisoning symptoms such as abdominal discomfort and diarrhea, causing allergic dermatitis or eczema; if it is brought into the human body by breathing, it will irritate and corrode the respiratory tract, causing pharyngitis, bronchitis, etc. Residents in severely polluted areas who often come into contact with or ingest excessive amounts of Cr(VI) are prone to rhinitis, tuberculosis, diarrhea, bronchitis and dermatitis, which seriously endanger human health. Therefore, removing Cr(VI) from wastewater has important environmental significance. Among the various adsorption materials for treating wastewater containing Cr(VI) by adsorption, activated carbon-based materials have the advantages of a wide range of raw material sources and diverse preparation methods, but the commonly used non-renewable fossil fuels and complex preparation processes make them expensive (Advanced Materials, 2019, 31, 1900440).

[0003] Biomass carbon materials have the advantages of wide raw material sources, renewable, environmentally friendly, and strong plasticity of texture properties such as pore structure, so they have attracted attention in the field of heavy metal wastewater purification. For example, Maria et al. (Journal of Molecular Liquids, 2020, 317, 114262) used homemade gemini surfactants to modify peanut shells, and the maximum equilibrium adsorption capacity of the modified carbon material for Cr(VI) at room temperature was only 0.141 mmol / g. However, the homemade gemini surfactant is toxic and the synthesis process is very complicated. Therefore, it is of great significance to further explore and develop peanut shell-based carbon materials with high adsorption capacity for Cr(VI) and environmental friendliness.

[0004] A low eutectic solvent is a two-component or three-component low eutectic mixture composed of a certain stoichiometric ratio of hydrogen bond acceptors (such as quaternary ammonium salts) and hydrogen bond donors (such as compounds such as amides, carboxylic acids and polyols), and its freezing point is significantly lower than the melting point of each component pure substance. As a new type of solvent, it has the characteristics of simple preparation, low cost, low toxicity, good solubility, and low volatility. However, there are few reports on the preparation of peanut shell-based hydrothermal carbon materials using a low eutectic solvent-assisted one-step hydrothermal method. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a one-step hydrothermal modified biocarbon material with cheap raw materials and modified substances, simple preparation process, and excellent Cr(VI) adsorption performance. The biocarbon material has the advantages of large adsorption capacity and extremely fast adsorption kinetics for the adsorption of Cr(VI) in water, and can be used as a heavy metal ion adsorbent.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a type III deep eutectic solvent modified peanut shell-based hydrothermal carbon heavy metal ion adsorbent, the method comprising the following steps:

[0008] The peanut shell powder is added to a low eutectic solvent and mixed evenly to form a suspension. Water is then added to the suspension at room temperature and stirred for a period of time. After the stirring is completed, the mixture is subjected to a hydrothermal carbonization reaction. After the reaction is completed, the product is cooled to room temperature, the suspension is separated, and the filter cake is washed and dried to obtain hydrothermal carbon.

[0009] The deep eutectic solvents are choline chloride and urea.

[0010] The preparation method of the low eutectic solvent is as follows: choline chloride and urea are mixed according to a mass ratio, and stirred at 50° C. to form a transparent low eutectic solvent; the choline chloride is 2.78 to 9.73 parts by mass, and the urea is 2.40 to 8.40 parts by mass.

[0011] The preparation steps of the peanut shell powder are as follows: washing the peanut shell with deionized water until the filtrate is colorless, then drying the filter cake at 60° C. for 24 hours and grinding it through a 200-mesh sieve to obtain the peanut shell powder;

[0012] The mass ratio of the peanut shell powder to the low eutectic solvent is 1-4:5-20.

[0013] The ratio of the peanut shell powder to water is 1-4:25 g / mL.

[0014] The stirring refers to first ultrasonic stirring for 20 minutes (ultrasonic power of 180 W, ultrasonic frequency of 40 kHz), and then magnetic stirring (300 r / min) for 30 minutes.

[0015] The temperature of the hydrothermal carbonization reaction is 160-220°C, preferably 190-220°C.

[0016] The hydrothermal carbonization reaction time is 6 to 12 hours, preferably 9 to 12 hours.

[0017] The washing refers to washing with deionized water for 3 times and with anhydrous ethanol for 3 times, and the drying refers to drying at 60° C. for 24 hours.

[0018] The specific surface area of ​​the hydrothermal carbon prepared by the above method is 9.33-95.06 m 2 / g, average pore diameter of 11.16-21.48 nm, pore volume of 0.02-0.33 cm 3 / g, micropore volume is 0.0005~0.02cm 3 / g.

[0019] The hydrothermal carbon can be used for the adsorption of Cr(VI) in water. At room temperature, solution pH=2, and an initial Cr(VI) concentration of 0.5-300 mg / L, the equilibrium adsorption amount of Cr(VI) is 48.94-227.11 mg / g.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] (1) The present invention can use raw materials and reagents with wide sources and low prices, including peanut shells, choline chloride and urea.

[0022] (2) The preparation method adopted by the present invention is simple, and the dissolution, modification and hydrothermal carbonization of peanut shells can be achieved through only one hydrothermal step, which greatly simplifies the preparation process and improves efficiency.

[0023] (3) The hydrothermal carbon material prepared by the present invention has a large adsorption capacity for heavy metal ions Cr(VI) and fast adsorption kinetics, which has a certain reference value for the development of high-performance biomass hydrothermal carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD patterns of DPSHTC-1 to DPSHTC-6 prepared in Examples 1 to 6 and the XRD patterns of PSHTC-1 to PSHTC-2 prepared in Comparative Examples 1 to 2 are shown.

[0025] Figure 2 (a) N2 adsorption-desorption isotherms and (b) pore size distribution curves of DPSHTC-1, DPSHTC-2, PSHTC-1 and PSHTC-2 prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.

[0026] Figure 3 (a) N2 adsorption-desorption isotherms and (b) pore size distribution curves of DPSHTC-3, DPSHTC-4, DPSHTC-5 and DPSHTC-6 prepared in Examples 3, 4, 5 and 6.

[0027] Figure 4The adsorption kinetic curves of 100 mg of PSHTC-1, DPSHTC-2, PSHTC-1 and PSHTC-2 prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 on 100 mL of Cr(VI) solution with an initial concentration of 100 mg / L at pH = 2.

[0028] Figure 5 The adsorption kinetic curves of 100 mg of DPSHTC-3, DPSHTC-4, DPSHTC-5 and DPSHTC-6 prepared in Examples 3, 4, 5 and 6 on 100 mL of Cr(VI) solution with an initial concentration of 100 mg / L and pH=2. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.

[0030] Embodiment 1:

[0031] 9.73 g of choline chloride and 8.40 g of urea were mixed, stirred magnetically (300 r / min) at 50° C. to form a transparent low eutectic solvent, and then cooled to room temperature. 4.00 g of peanut shell powder was added to the low eutectic solvent and mixed to form a suspension. Subsequently, 25 mL of deionized water was added to the above suspension at room temperature, and ultrasonic stirring was performed for 20 minutes at an ultrasonic power of 180 W and an ultrasonic frequency of 40 kHz, followed by magnetic stirring (300 r / min) for 30 minutes. After stirring, the mixture was evenly transferred into a 100 mL stainless steel hydrothermal autoclave lined with polytetrafluoroethylene, and placed in a forced air drying oven for hydrothermal carbonization reaction at 220°C for 12 hours. After the product was cooled to room temperature, the suspension was separated, and the filter cake was washed three times with deionized water and then with anhydrous ethanol. After the washed filter cake was dried in an oven at 60°C for 24 hours, a peanut shell-based hydrothermal carbon material modified with a Class III low eutectic solvent (choline chloride / urea) was obtained, which was named DPSHTC-1.

[0032] The specific surface area of ​​the DPSHTC-1 obtained above is 70.31 m 2 / g, average pore diameter of 13.96nm, pore volume of 0.25cm 3 / g, micropore volume is 0.0006cm 3 / g.

[0033] When 100 mg of the above DPSHTC-1 was used to adsorb a solution with a pH of 2 and an initial Cr(VI) concentration of 0.5 to 300 mg / L at room temperature, the time to reach equilibrium was 2 to 3 hours, and the equilibrium adsorption amount of Cr(VI) was 220.51 mg / g; the adsorption amount of Cr(VI) reached 89.29% of the equilibrium amount after 30 minutes of adsorption. Under the same conditions, the residual concentration of Cr(VI) was 0 mg / L after 100 mg of the sample was used to adsorb 100 mL of a 0.5 mg / L Cr(VI) solution.

[0034] Comparative Example 1:

[0035] 9.73g of choline chloride, 8.40g of urea and 4.00g of peanut shell powder were mixed to form a suspension. Subsequently, 25mL of ionized water was added to the suspension at room temperature, and ultrasonic stirring was performed for 20min at an ultrasonic power of 180W and an ultrasonic frequency of 40kHz, followed by magnetic stirring (300r / min) for 30min; after stirring, the mixture was transferred to a 100mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and placed in a blast drying oven for a hydrothermal reaction at 220°C for 12h; after the product was cooled to room temperature, the suspension was separated, the filter cake was washed 3 times with deionized water and then 3 times with anhydrous ethanol, and the washed filter cake was dried in an oven at 60°C for 24h to obtain a peanut shell-based hydrothermal carbon material, named PSHTC-1.

[0036] The specific surface area of ​​the PSHTC-1 prepared above is 47.53 m 2 / g, average pore diameter of 16.82nm, pore volume of 0.20cm 3 / g, micropore volume is 0.0005cm 3 When 100 mg of the above PSHTC-1 was taken to adsorb a solution with a pH of 2 and an initial Cr(VI) concentration of 0.5 to 300 mg / L at room temperature, the time for adsorption to reach equilibrium was 7 to 8 hours, and the equilibrium adsorption amount of Cr(VI) was 76.66 mg / g.

[0037] Embodiment 2:

[0038] 2.78 g of choline chloride and 2.40 g of urea were mixed, stirred magnetically (300 r / min) at 50° C. to form a transparent low eutectic solvent, and then cooled to room temperature. 2.00 g of peanut shell powder was added to the low eutectic solvent and mixed to form a suspension. Subsequently, 25 mL of deionized water was added to the above suspension at room temperature, and ultrasonic stirring was performed for 20 minutes at an ultrasonic power of 180 W and an ultrasonic frequency of 40 kHz, and then magnetic stirring (300 r / min) was performed for 30 minutes; after the stirring was completed, the mixture was transferred to a 100 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and placed in a forced air drying oven for a hydrothermal reaction at 220°C for 12 hours; after the product was cooled to room temperature, the suspension was separated, the filter cake was washed 3 times with deionized water and then washed 3 times with anhydrous ethanol, and the washed filter cake was dried in an oven at 60°C for 24 hours to obtain a peanut shell-based hydrothermal carbon material modified with a Class III low eutectic solvent (choline chloride / urea), named DPSHTC-2.

[0039] The specific surface area of ​​the above DPSHTC-2 is 95.06m 2 / g, average pore diameter of 13.82nm, pore volume of 0.33cm 3 / g, micropore volume is 0.001cm 3 / g. When 100 mg of the above DPSHTC-2 was taken at room temperature to adsorb a solution with pH = 2 and an initial Cr(VI) concentration of 0.5-300 mg / L, the time required for the adsorption to reach equilibrium was 2-3 hours, and the equilibrium adsorption amount of Cr(VI) was 227.11 mg / g; when the adsorption time was 30 minutes, the adsorption amount of Cr(VI) reached 89.03% of the equilibrium. Under the same conditions, after 100 mg of the sample was used to adsorb 100 mL of 0.5 mg / L Cr(VI) solution, the residual concentration of Cr(VI) was 0 mg / L.

[0040] Comparative Example 2:

[0041] 25 mL of deionized water was added to 2.00 g of peanut shell powder at room temperature, and ultrasonic stirring was performed for 20 min at a power of 180 W and a frequency of 40 kHz, followed by magnetic stirring (300 r / min) for 30 min. After stirring, the mixture was transferred into a 100 mL stainless steel hydrothermal autoclave lined with polytetrafluoroethylene, and placed in a forced air drying oven for a hydrothermal reaction at 220 ° C for 12 h. After the product was cooled to room temperature, the suspension was separated, the filter cake was washed 3 times with deionized water and then with anhydrous ethanol 3 times, and the washed filter cake was dried at 60 ° C for 24 h to obtain a peanut shell-based hydrothermal carbon material, named PSHTC-2.

[0042] The specific surface area of ​​the above PSHTC-2 is 27.17 m 2 / g, average pore diameter of 21.48nm, pore volume of 0.14cm3 / g, micropore volume is 0.002cm 3 When 100 mg of the above PSHTC-2 was taken at room temperature to adsorb a solution with a pH of 2 and an initial Cr(VI) concentration of 0.5 to 300 mg / L, the time required for the adsorption to reach equilibrium was 7 to 8 hours, and the equilibrium adsorption amount was 49.48 mg / g.

[0043] Embodiment 3:

[0044] 5.56g of choline chloride and 4.80g of urea were mixed, stirred magnetically (300r / min) at 50°C to form a transparent low eutectic solvent, and then cooled to room temperature. 1.00g of peanut shell powder was added to the low eutectic solvent and mixed to form a suspension. Subsequently, 25mL of deionized water was added to the above suspension at room temperature, and ultrasonic stirring was first performed for 20min at a power of 180W and a frequency of 40kHz, followed by magnetic stirring for 30min (300r / min). After stirring, the mixture was transferred to a 100mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and a hydrothermal reaction was performed at 220°C in a blast drying oven for 12h; after the product was cooled to room temperature, the suspension was separated, the filter cake was washed 3 times with deionized water and then washed 3 times with anhydrous ethanol, and the washed filter cake was dried in an oven at 60°C for 24h to obtain a peanut shell-based hydrothermal carbon material modified by a Class III low eutectic solvent (choline chloride / urea), named DPSHTC-3.

[0045] The specific surface area of ​​the above DPSHTC-3 is 57.15m 2 / g, average pore diameter of 11.44nm, pore volume of 0.16cm 3 / g, micropore volume is 0.001cm 3 / g.

[0046] When 100 mg of the above DPSHTC-3 was taken at room temperature to adsorb a Cr(VI) solution with a pH of 2 and an initial concentration of 0.5-300 mg / L, the time required for the adsorption to reach equilibrium was 2-3 hours, and the equilibrium adsorption amount of Cr(VI) was 225.38 mg / g; after adsorption for 30 minutes, the adsorption amount of Cr(VI) reached 86.94% of the equilibrium amount. Under the same conditions, after 100 mg of the sample was used to adsorb 100 mL of a 0.5 mg / L Cr(VI) solution, the residual concentration of Cr(VI) was 0 mg / L.

[0047] Embodiment 4:

[0048] 2.78 g of choline chloride and 2.40 g of urea were mixed, stirred magnetically (300 r / min) at 50° C. to form a transparent low eutectic solvent, and then cooled to room temperature. 2.00 g of peanut shell powder was added to the low eutectic solvent and mixed to form a suspension. Subsequently, 25 mL of deionized water was added to the above suspension at room temperature, and ultrasonic stirring was performed for 20 minutes at a power of 180 W and a frequency of 40 kHz, followed by magnetic stirring for 30 minutes (300 r / min). After stirring, the mixture was transferred into a 100 mL stainless steel hydrothermal autoclave lined with polytetrafluoroethylene, and placed in a forced air drying oven for a hydrothermal reaction at 160°C for 12 hours. After the product was cooled to room temperature, the suspension was separated, and the filter cake was washed three times with deionized water and then with anhydrous ethanol. After the washed filter cake was dried in an oven at 60°C for 24 hours, a peanut shell-based hydrothermal carbon material modified by a Class III low eutectic solvent (choline chloride / urea) was obtained, which was named DPSHTC-4.

[0049] The specific surface area of ​​the above DPSHTC-4 is 9.33m 2 / g, average pore diameter of 11.97nm, pore volume of 0.02cm 3 / g, micropore volume is 0.0002cm 3 / g.

[0050] When 100 mg of the above DPSHTC-4 is taken at room temperature to adsorb a Cr(VI) solution with a pH of 2 and an initial concentration of 0.5 to 300 mg / L, the time required for the adsorption to reach equilibrium is 8 to 9 hours, and the equilibrium adsorption amount of Cr(VI) is 48.94 mg / g.

[0051] Embodiment 5:

[0052] 5.56 g of choline chloride and 4.80 g of urea were mixed, stirred magnetically (300 r / min) at 50° C. to form a transparent low eutectic solvent, and then cooled to room temperature. 1.00 g of peanut shell powder was added to the low eutectic solvent and mixed to form a suspension. Subsequently, 25 mL of deionized water was added to the above suspension at room temperature, and ultrasonic stirring was performed for 20 minutes at a power of 180 W and a frequency of 40 kHz, followed by magnetic stirring for 30 minutes (300 r / min). After stirring, the mixture was transferred into a 100 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and placed in a blast drying oven for a hydrothermal reaction at 220°C for 6 hours. After the product was cooled to room temperature, the suspension was separated, and the filter cake was washed three times with deionized water and then with anhydrous ethanol. After the washed filter cake was dried in an oven at 60°C for 24 hours, a peanut shell-based hydrothermal carbon material modified with a Class III low eutectic solvent (choline chloride / urea) was obtained, which was named DPSHTC-5.

[0053] The specific surface area of ​​the above DPSHTC-5 is 63.06m2 / g, average pore diameter of 11.16nm, pore volume of 0.18cm 3 / g, micropore volume is 0.001cm 3 / g.

[0054] When 100 mg of the above DPSHTC-5 was taken at room temperature to adsorb a Cr(VI) solution with a pH of 2 and an initial concentration of 0.5 to 300 mg / L, the time required for the adsorption to reach equilibrium was 4 to 5 hours, and the equilibrium adsorption amount was 86.76 mg / g. In this embodiment, due to the shortening of the hydrothermal reaction time, the reaction was not fully carried out, which resulted in a lower yield of functional groups on the surface of the material than in Example 3. Therefore, the Cr(VI) equilibrium adsorption amount of the material prepared in this embodiment was lower than that in Example 3.

[0055] Embodiment 6:

[0056] 6.95 g of choline chloride and 6.00 g of urea were mixed, stirred magnetically (300 r / min) at 50° C. to form a transparent low eutectic solvent, and then cooled to room temperature. 3.00 g of peanut shell powder was added to the low eutectic solvent and mixed to form a suspension. Subsequently, 25 mL of deionized water was added to the above suspension at room temperature, and ultrasonic stirring was performed for 20 minutes at a power of 180 W and a frequency of 40 kHz, followed by magnetic stirring for 30 minutes (300 r / min). After stirring, the mixture was transferred into a 100 mL stainless steel hydrothermal autoclave lined with polytetrafluoroethylene, and placed in a blast drying oven for a hydrothermal reaction at 190°C for 9 hours. After the product was cooled to room temperature, the suspension was separated, and the filter cake was washed three times with deionized water and then with anhydrous ethanol. After the washed filter cake was dried in an oven at 60°C for 24 hours, a peanut shell-based hydrothermal carbon material modified with a Class III low eutectic solvent (choline chloride / urea) was obtained, which was named DPSHTC-6.

[0057] The specific surface area of ​​the above DPSHTC-6 is 29.41m 2 / g, average pore diameter of 11.86nm, pore volume of 0.08cm 3 / g, micropore volume is 0.002cm 3 / g.

[0058] When 100 mg of the above DPSHTC-6 was taken at room temperature to adsorb a Cr(VI) solution with a pH of 2 and an initial concentration of 0.5-300 mg / L, the time required for the adsorption to reach equilibrium was 6-7 h, and the equilibrium adsorption amount was 96.55 mg / g.

[0059] Table 1. Data of samples prepared in various embodiments

[0060]

[0061] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a type III deep eutectic solvent modified peanut shell-based hydrothermal carbon heavy metal ion adsorbent, characterized in that: The method comprises the following steps: The peanut shell powder is added to a low eutectic solvent and mixed evenly to form a suspension, and then water is added to the suspension at room temperature and stirred for a period of time. After the stirring is completed, the mixture is subjected to a hydrothermal carbonization reaction. After the reaction is completed, the product is cooled to room temperature, the suspension is separated, and the filter cake is washed and dried to obtain hydrothermal carbon.

2. The method according to claim 1, characterized in that The preparation method of the low eutectic solvent is as follows: choline chloride and urea are mixed according to a mass ratio, and stirred at 50° C. to form a transparent low eutectic solvent; the choline chloride is 2.78 to 9.73 parts by mass, and the urea is 2.40 to 8.40 parts by mass.

3. The method according to claim 1, characterized in that The preparation steps of the peanut shell powder are as follows: washing the peanut shell with deionized water until the filtrate is colorless, and then drying the filter cake at 60° C. for 24 hours and grinding it through a 200-mesh sieve to obtain the peanut shell powder.

4. The method according to claim 1, characterized in that: The mass ratio of the peanut shell powder to the low eutectic solvent is 1-4:5-20.

5. The method according to claim 1, characterized in that: The stirring refers to first ultrasonic stirring for 20 minutes and then magnetic stirring for 30 minutes.

6. The method according to claim 1, characterized in that The temperature of the hydrothermal carbonization reaction is 160-220° C., and the time of the hydrothermal carbonization reaction is 6-12 hours.

7. The method according to claim 6, characterized in that The temperature of the hydrothermal carbonization reaction is 190-220° C., and the time of the hydrothermal carbonization reaction is 9-12 hours.

8. The method according to claim 1, characterized in that The washing refers to washing with deionized water for 3 times and with anhydrous ethanol for 3 times, and the drying refers to drying at 60° C. for 24 hours.

9. A modified peanut shell-based hydrothermal carbon prepared by the method according to any one of claims 1 to 8.

10. Use of the modified peanut shell-based hydrothermal carbon according to claim 9 as a heavy metal ion adsorbent.